Angiotensin IV possibly acts through PKMzeta in the hippocampus to regulate cognitive memory in rats. (October 2015) - Chow, Lok-Hi; Tao, Pao-Luh; Chen, Yuan-Hao; Lin, Yu-Hui; Huang, Eagle Yi-Kung
Abstract: Ang IV is an endogenous peptide generated from the degradation of angiotensin II. Ang IV was found to enhance learning and memory in CNS. PKMzeta was identified to be a fragment of PKCzeta (protein kinase Czeta). Its continuous activation was demonstrated to be correlated with the formation of memory in the hippocampus. Therefore, we investigated whether PKMzeta participates in the effects of Ang IV on memory. We first examined the effect of Ang IV on non-spatial memory/cognition in modified object recognition test in rats. Our data showed that Ang IV could increase the exploration time on novel object. The co-administration of ZIP (PKMzeta inhibitor) with Ang IV significantly blocked the effect by Ang IV. The effects of Ang IV on hippocampal LTP at the CA1 region were also evaluated. Ang IV significantly increased the amplitude and slope of the EPSPs, which was consistent with other reports. Surprisingly, instead of potentiating LTP, Ang IV caused a failed maintenance of LTP. Moreover, there was no quantitative change in PKMzeta induced by Ang IV and/or ZIP after behavioral experiments. Taken together, our data re-confirmed the finding of the positive effect of Ang IV to enhance memory/cognition. The increased strength of EPSPs with Ang IV could also have certain functional relevance. Since the behavioral results suggested the involvement of PKMzeta, we hypothesized that the enhancement of memory/cognition by Ang IV may rely on an increase in PKMzeta activity. Overall, the present study provided important advances in our understanding of the action of Ang IV in the hippocampus. Highlights: Central Ang IV produced an enhancement of cognitive memory in mORT in rats. Memory enhancement by Ang IV could be related to PKMzeta activation. Ang IV potentiated EPSP in the hippocampus, but not LTP in our recording model.